ANALISIS KEKUATAN GIRDER AKIBAT KEMIRINGAN MEMANJANG JEMBATAN - Suyadi Suyadi (UNIVERSITAS LAMPUNG, 2014)
At standards, the maximum slope of the bridge is 5%. Longitudinal slope of the bridge will determine the length of the bridge, more sloping more length. Its became more greater the cost. The reasons that underlie this analysis. The analysis has been performed on three kinds of bridges that T beam bridge, PCI bridge and bridge steel truss girder models Callendar Hamilton. The analysis was performed in the manual method and software SAP 2000. This Analysis focused on the capacity of the cross-sectional of the withstand stresses caused by the load acting on the bridge. The bridge is modeled in some slope ranging from 0% for the comparison, 2.5%; 5%; 7.5% and 10%. To easy analysis, load to be projected in the two direction at sloping bridges. It is seen that more greater of the slope cause axial force on girder bridges is increasing. The analysis considering of the combination of axial load, shear and bending ascpects From the analysis looks at three kinds of bridges, with a slope of up to 10% were still able to support the load of the bridge there. It is necessary to do advance analysis of the bridge’s ability and the other element of bridges that direct contact with the longitudinal girder bridge girders due